A new structure of p-GaN/InGaN heterojunction to enhance hole injection for blue GaN-based LEDs. (21st June 2016) - Lin, Zhiting; Wang, Haiyan; Lin, Yunhao; Yang, Meijuan; Li, Guoqiang; Xu, Bingshe
Abstract: A new structure of p-GaN/InGaN heterojunction has been proposed to enhance hole injection for blue GaN-based light-emitting diodes (LEDs). It is demonstrated by the simulation results that a p-GaN (50 nm)/In0.05 Ga0.95 N (150 nm) heterojunction can make a 25% and 10% increment of hole and electron concentration in the active region, respectively, finally resulting in a 55% improvement on the LED's radiative recombination intensity. The simulation also reveals that the efficiency droop is alleviated from 32.9% to 21.7% at the current density of 100 A cm −2 . The enhanced hole injection is mainly attributed to the increased average background hole concentration of the area between the p-AlGaN electron blocking layer (EBL) to the p-GaN/InGaN heterojunction. The increasing potential barrier of the conduction band, resulting from the introduction of p-GaN/InGaN heterojunction, would also weaken electron leakage and is favorable to the LED's luminous performance. The experimental results show that the wall-plug efficiency (WPE) of the p-GaN/InGaN LED increases by 26.0% at the injection current of 75 mA, in spite of the increasing electric resistance, which impairs the improvement of the LED's performance from the enhanced hole injection. The structure of the p-GaN/InGaN heterojunction is novel in the field of p-type region design, and is a simple but effective way to promote the LED's performance, which is very promising for application in further high-performance LED fabrication.